Granular materials
A particulate material with elemental silver and ruthenium on a water-insoluble carrier, achieving a light color and antimicrobial efficacy, addresses the color limitation of existing dark materials, enabling use on bright-colored surfaces.
Patent Information
- Application Number
- JP2024522712
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-11-26
- Filing Date
- 2022-07-20
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-07-20
AI Technical Summary
Existing antimicrobial particulate materials with elemental silver and ruthenium have a dark or black color, limiting their application on light-colored materials and objects.
A particulate material comprising 15% to 50% elemental silver and elemental ruthenium on a water-insoluble carrier material, with 50% to 85% of solids such as aluminum oxide or titanium dioxide, achieving a lightness range of 50 to 85, allowing use on bright-colored surfaces.
The material maintains antimicrobial efficacy while providing a lighter color suitable for use on light-colored materials and objects, enhancing applicability.
Smart Images

Figure 2024545844000001 
Figure 2024545844000002 
Figure 2024545844000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a particulate material (powder) composed of a water-insoluble carrier material with elemental silver and elemental ruthenium, with a solid at least partially disposed on the particles. The solid is selected from the group consisting of aluminum oxide, aluminum hydroxide, aluminum oxyhydroxide, magnesium oxide, magnesium hydroxide, magnesium oxyhydroxide, calcium oxide, calcium hydroxide, calcium oxyhydroxide, silicon dioxide, silica, zinc oxide, zinc hydroxide, zinc oxyhydroxide, zirconium dioxide, zirconium (IV) oxyhydrate, titanium dioxide, titanium (IV) oxyhydrate, and combinations thereof. The present invention also relates to a method for preparing the particulate material, and to its use. Summary of the Invention [Problem to be solved by the invention]
[0002] WO 2021 / 084140A2 discloses a particulate carrier material that can be used as an additive for the antimicrobial treatment of many different materials and that can comprise elemental silver and elemental ruthenium. This material has a corresponding low lightness L * (e.g., in the range of 35 to 45). Dark colors can limit the usefulness of antimicrobial treatment of light materials and objects.
[0003] US Patent No. 5,985,466 discloses a powder having a metal oxide film on its surface, which has an increased refractive index and therefore a high reflectivity and a bright color. The powder includes substrate particles having a multilayer film on its surface, which includes at least one metal oxide layer. The method of preparing the powder includes dispersing the substrate particles in a solution of a metal alkoxide, hydrolyzing the metal alkoxide to obtain a metal oxide, precipitating a film of the metal oxide on the surface of the substrate particles, performing these steps two or more times to form a multilayer metal oxide film, and performing a heat treatment at least in the last step. The multilayer metal oxide film is thereby adjusted to have a suitable combination of constituent materials and a suitable film thickness in order to change the interference color of the multilayer film and to impart a bright color to the powder.
[0004] The lightness L referred to in this specification and claims * is CIEL * a * b * L in color space (DIN EN ISO / CIE 11664-4:2020-03) * and is determined spectrophotometrically in a measurement geometry of d / 8°. Spectrophotometric measurements of powder materials can be carried out on material samples filled into a colorless glass container with a filling height of 1 cm through the flat glass bottom of the glass container which is placed on the measuring head of the spectrophotometer used.
[0005] The present invention described below solves the aforementioned color or brightness problem by providing a particulate material that can be used as an antimicrobial additive and has a relatively light color, in particular a lighter color than the materials disclosed in WO 2021 / 084140 A2. Due to its light color, the particulate material according to the invention is also suitable for the antimicrobial design of materials and objects that have a relatively light color.
[0006] The present invention relates to a particulate material Z consisting of 15% to 50% by weight of particles X of a water-insoluble support material T provided with elemental silver and elemental ruthenium, and 50% to 85% by weight of a solid Y at least partially disposed on the particles X, the solid Y being selected from the group consisting of aluminum oxide, aluminum hydroxide, aluminum oxyhydroxide, magnesium oxide, magnesium hydroxide, magnesium oxyhydroxide, calcium oxide, calcium hydroxide, calcium oxyhydroxide, silicon dioxide, silica, zinc oxide, zinc hydroxide, zinc oxyhydroxide, zirconium dioxide, zirconium(IV) oxyhydrate, titanium dioxide, titanium(IV) oxyhydrate, and combinations thereof. The weight percentages of components X and Y add up to 100% by weight. The selection of the X:Y weight ratio within the range according to the invention is dependent on the color or lightness L of the particulate material Z according to the invention. * The particulate material Z according to the invention has a lightness L in the range of, for example, 50 to 85. * The proportion of silver + ruthenium in the particulate material Z may be, for example, in the range of 0.015% by weight to 25% by weight.
[0007] The solid Y constitutes 50% to 85% by weight of the particulate material Z according to the invention and is at least partially disposed on the particles X of the particulate material Z according to the invention, i.e. a certain proportion of the 50% to 85% by weight of the solid Y can be present "free" as free solid Y in addition to the particles X on which the solid Y is disposed and optionally the particles X on which the solid Y is not disposed. Thus, when viewed using a scanning electron microscope, the particulate material Z according to the invention substantially comprises or consists of a mixture of the particles X on which the solid Y is disposed and the free solid Y. The proportion of the free solid Y in the total amount of the solid Y can be, for example, in the range of 10% to less than 100% by weight, for example in the range of 10% to 90% by weight.
[0008] Solid Y is selected from the group consisting of aluminum oxide, aluminum hydroxide, aluminum oxyhydroxide, magnesium oxide, magnesium hydroxide, magnesium oxyhydroxide, calcium oxide, calcium hydroxide, calcium oxyhydroxide, silicon dioxide, silica, zinc oxide, zinc hydroxide, zinc oxyhydroxide, zirconium dioxide, zirconium (IV) oxyhydrate, titanium dioxide, titanium (IV) oxyhydrate, and combinations thereof. Titanium dioxide, titanium (IV) oxyhydrate, or combinations thereof, especially titanium dioxide, are preferred. Solid Y has a particulate morphology, i.e. both the free solid Y and the solid Y arranged on the particles X are formed as particles. In other words, solid Y is not layered, it does not form any layer or coating in the sense of a closed layer. Thus, but in other words, particle X does not have a single or multi-layer coating, in particular a single or multi-layer coating, one or more layers of which comprise or consist of solid Y.
[0009] Solid Y placed on particle X adheres to particle X and cannot be easily separated from particle X, for example by washing or shaking. The adhesion of solid Y onto particle X is essentially physical in nature, although the possible formation of chemical bonds cannot be excluded.
[0010] Particles X consist of particles of a water-insoluble support material T with elemental silver and elemental ruthenium. With elemental silver and elemental ruthenium means that silver and ruthenium can be present on the inner surface (in the pores and / or cavities) and / or on the outer surface of the support material particles depending on the type of support material T, thereby forming, for example, a continuous or discontinuous layer and / or small silver or ruthenium particles. Silver and ruthenium are attached to the surface of the support material particles, and the attachment is essentially physical in nature, although the possible formation of chemical bonds cannot be excluded. Silver and ruthenium are not alloyed, but rather randomly distributed. It is clear to the skilled person that silver and ruthenium on the surface can also include other silver species than elemental metallic silver and other ruthenium species than elemental metallic ruthenium, for example the corresponding oxides and / or halides and / or sulfides. The particles X of a water-insoluble support material T provided with elemental silver and elemental ruthenium may in particular have a silver+ruthenium weight proportion ranging from 0.1% to 50% by weight, with a silver:ruthenium weight ratio ranging from 1 part by weight to 2,000 parts by weight of silver:1 part by weight of ruthenium.
[0011] The fact that the water-insoluble carrier material T of particles X exists in an agglomerated solid state will be apparent to those skilled in the art.
[0012] The support material particles T can have a wide variety of particle shapes. For example, they can be irregularly shaped or they can have a defined shape. They can be, for example, spherical, ellipsoidal, platelet-shaped or rod-shaped. The support material particles T can be porous and / or have cavities or none of these. They can have a smooth, rough or structured outer surface. The support material particles can have an average particle size (d50) in the range of, for example, 0.4 μm to 100 μm. The absolute particle size of the support material particles T is generally less than 0.1 μm and generally does not exceed 1,000 μm.
[0013] The term "average particle size" as used herein means the average particle size (d50) that can be determined by laser diffraction. Laser diffraction measurements can be performed using a corresponding particle size measuring device, for example the Mastersizer 3000 from Malvern Instruments.
[0014] The water-insoluble particulate carrier material T has a more or less large water absorption capacity between the particles and possibly also within the particles, for example within the pores and / or recesses of the particle surface. The water-insoluble particulate carrier material T may be swellable with water or even capable of forming a hydrogel. It is not attacked, dissolved or its properties as a carrier material T are impaired by water. The water-insoluble actual carrier material T itself is preferably a non-water-repellent material. It is preferably hydrophilic, but in any case water-insoluble, as described. The actual carrier material T may also be a material in the form of particles, for example a powder, selected from inorganic or organic substances or materials. For the avoidance of doubt, the carrier material T is a silver-free and ruthenium-free substance or a silver-free and ruthenium-free material. The carrier material T is preferably neither magnetic nor magnetizable, it is not carbonyl iron. Examples of support materials of type T include glass; nitrides, such as aluminum nitride, titanium nitride, silicon nitride; high-melting oxides, such as aluminum oxide, titanium dioxide, silicon dioxide, for example as silica or quartz; silicates, such as sodium aluminum silicate, zirconium silicate, zeolites; plastic materials, such as (meth)acrylic homo- and copolymers and polyamides; modified or unmodified naturally occurring polymers, such as polysaccharides and polysaccharide derivatives, in particular cellulose and cellulose derivatives; carbon substrates, in particular porous carbon substrates; and wood. The water-insoluble support material T of the particles X may be the same as or different from the solid Y. Silicon dioxide, titanium dioxide, and cellulose are preferred support materials T, in the case of cellulose, in particular in the form of linear cellulose fibers, for example with fiber lengths in the range of 10 μm to 1,000 μm.
[0015] The particles X, which are made of a water-insoluble carrier material T provided with elemental silver and elemental ruthenium, are free-flowing (non-agglomerating) powders. The free-flowing nature of the free-flowing powders can be determined by the Rotational Powder Analysis method described below.
[0016] The particles X of a water-insoluble support material T provided with elemental silver and elemental ruthenium may be, for example, a material of the type disclosed in WO 2021 / 084140 (A2). WO 2021 / 084140 (A2) also discloses a method for preparing a particulate support material of type X provided with elemental silver and elemental ruthenium. For the sake of brevity, explicit reference is made in this respect to the disclosure of WO 2021 / 084140 (A2), page 2, line 6 to page 13, line 17, both with regard to this material and with regard to this preparation method.
[0017] The particulate material Z according to the invention can be produced by contacting particles X consisting of a water-insoluble support material T provided with elemental silver and elemental ruthenium with at least one C1-C4 alkoxide of aluminium, magnesium, calcium, silicon, zinc, zirconium and / or titanium in the presence of water in an amount at least sufficient for the complete hydrolysis of the at least one C1-C4 alkoxide. In this respect, the invention also relates to such a preparation method.
[0018] As mentioned above, the particulate material Z according to the invention can be prepared by complete hydrolysis of at least one C1-C4 alkoxide of aluminum, magnesium, calcium, silicon, zinc, zirconium and / or preferably titanium in the presence of particles X, i.e. the method for preparing the particulate material Z according to the invention comprises complete hydrolysis of at least one C1-C4 alkoxide of aluminum, magnesium, calcium, silicon, zinc, zirconium and / or preferably titanium in the presence of particles X. In other words, the method for preparing the particulate material Z according to the invention comprises contacting particles X with at least one C1-C4 alkoxide of aluminum, magnesium, calcium, silicon, zinc, zirconium and / or preferably titanium in the presence of water in an amount at least sufficient for complete hydrolysis of said at least one C1-C4 alkoxide. The C1-C4 alkoxide of aluminum, magnesium, calcium, silicon, zinc, zirconium and / or preferably titanium is preferably prepared by the complete hydrolysis of aluminum trialkoxide Al(OC n H 2n+1 ) 3 , magnesium dialkoxide Mg(OC n H 2n+1 ) 2 , Calcium dialkoxide Ca(OC n H 2n+1 ) 2 , silicon tetraalkoxide Si(OC n H 2n+1 ) 4 , zinc dialkoxide Zn(OC n H 2n+1 ) 2 , zirconium tetraalkoxide Zr(OC n H 2n+1 ) 4 and / or preferably titanium tetraalkoxide Ti(OC n H 2n+1 ) 4 where n=1, 2, 3 or 4 in each case, preferably 3. In the preferred case where n=3, isopropoxides, in particular titanium tetraisopropoxide Ti[OCH(CH), also called TTIP, are 3 ) 2] 4 It is particularly preferred to work with . TTIP is preferably used alone. Since the hydrolysis proceeds quantitatively, it is simple for the skilled person responsible for the preparation of the particulate material Z according to the invention to make a quantitative selection according to stoichiometric considerations for at least one C1-C4 alkoxide of aluminum, magnesium, calcium, silicon, zinc, zirconium and / or preferably titanium, as well as for the particles X. For this complete hydrolysis, the skilled person will select at least 1 mole of water per mole of C1-C4 alkoxide of magnesium, calcium or zinc to be hydrolyzed, at least 1.5 moles of water per mole of C1-C4 alkoxide of aluminum to be hydrolyzed, and at least 2 moles of water per mole of C1-C4 alkoxide of silicon, zirconium or titanium, as explained below. Water can be provided as atmospheric moisture, as the moisture content of the particles X and / or in liquid form, in an amount of water that is at least sufficient for the complete hydrolysis of at least this at least one C1-C4 alkoxide, but which is generally a superstoichiometric quantitative proportion of water for this hydrolysis reaction.
[0019] For the sake of brevity, the expression "C1-C4 alkoxides of aluminum, magnesium, calcium, silicon, zinc, zirconium and / or preferably titanium" is also referred to below simply as "alkoxides".
[0020] According to the invention, the particles X can be contacted with at least one alkoxide in the presence of at least a sufficient amount of water for complete hydrolysis. The alkoxide is hydrolyzed to form the corresponding C1-C4 alcohol and the corresponding solid Y selected from the group consisting of aluminum oxide, aluminum hydroxide, aluminum oxyhydroxide, magnesium oxide, magnesium hydroxide, magnesium oxyhydroxide, calcium oxide, calcium hydroxide, calcium oxyhydroxide, silicon dioxide, silica, zinc oxide, zinc hydroxide, zinc oxyhydroxide, zirconium dioxide, zirconium (IV) oxyhydrate, titanium dioxide, titanium (IV) oxyhydrate, and combinations thereof. This allows the solid Y to be proportionally attached to the particles X. As a result, a particulate material Z according to the invention is formed as process product. After hydrolysis, the obtained product can be subjected to one or more further process steps, if necessary. Examples of such process steps include, inter alia, solid-liquid separation, washing, drying, and grinding.
[0021] The method according to the present invention, particularly the hydrolysis, can be carried out, for example, at a temperature range of 0°C to 80°C, preferably 20°C to 40°C.
[0022] In a first embodiment of the method according to the invention, the particles X can be directly contacted with at least one alkoxide. In this first embodiment of the method according to the invention, the particles X can be dry or anhydrous or can have a water content, for example in the form of residual moisture, for example in the range of more than 0% to 40% by weight. The at least one alkoxide can be used undiluted or diluted with a water-dilutable organic solvent, for example as a solution in a water-dilutable organic solvent. Such a preparation or solution can have, for example, a weight proportion of the at least one alkoxide in the range of 20% to less than 100% by weight, preferably 50% to 70% by weight. Examples of suitable water-dilutable organic solvents are in particular C1-C3 alcohols, in particular ethanol. In the following, "at least one alkoxide, optionally diluted" is also referred to in the shorter form "at least one alkoxide" for the sake of brevity.
[0023] In a first embodiment of the method according to the invention, water itself is not added at any point, and hydrolysis can take place under the influence of atmospheric moisture and any moisture present in the particles X. The atmospheric moisture can of course be the general atmospheric moisture or can be artificially set to a desired value, and the ingress of air can, if desired, be forced by deliberate air supply.
[0024] In a first embodiment of the method according to the invention, the particles X, which may have moisture, and at least one alkoxide, optionally diluted, are brought into contact with each other to form a pulp-like, pasty or dough-like mass, a suspension or preferably a free-flowing impregnated particulate material. The at least one alkoxide, optionally diluted, constitutes here the impregnating agent. The particles X can be added to the at least one alkoxide or vice versa. The at least one alkoxide is preferably added to the particles X previously provided. After the addition is finished, the reaction mixture can be conveniently given a further time, for example in the range of 0.5 h to 3 h, before further process steps are carried out. In this way, the completeness of the hydrolysis reaction and the homogenization of the reaction mixture can be ensured. Generally, mixing is carried out during and also after the addition. Examples of suitable mixing methods depend on the nature of the mixed materials and can therefore include, for example, shaking, stirring and / or kneading. In the preferred case of a mixed material in the form of a free-flowing impregnated particulate material, powder mixing methods operating continuously or discontinuously known to the skilled person are suitable, for example mixing in drum mixers, tumble mixers, pressure filters operating without pressure and having stirring devices, or vacuum mixer dryers operating in vacuum-free conditions and without heating. The expression "free-flowing impregnated particulate material" as used herein denotes a material in the form of impregnated grains or flakes, each of which may contain one or more particles X. A free-flowing impregnated particulate material is not a liquid, liquid dispersion or suspension, rather it is a free-flowing material in the form of a free-flowing powder. Its free flowability, or generally the free flowability of a free-flowing powder, can be investigated by rotational powder analysis. For this purpose, a cylindrical measuring drum can be filled with a given volume of the free-flowing impregnated particulate material. The measuring drum has a given diameter and a given depth. The measuring drum rotates around a horizontally oriented cylindrical axis at a given constant speed. One of the two end faces of the cylinder which together enclose the free-flowing impregnated particulate material packed in a cylindrical measuring drum is transparent. Before the start of the measurement, the measuring drum is rotated for 60 seconds.In the actual measurement, images of the free-flowing impregnated particulate material are then taken during rotation along the axis of rotation of the measuring drum using a camera with a high frame rate, for example 5 images / s to 15 images / s. The camera parameters can be selected so that the highest possible contrast is obtained at the material-air interface. During the rotation of the measuring drum, the free-flowing impregnated particulate material is brought up to a certain height against gravity and then falls to the bottom of the drum. The fall occurs in a sliding manner (discontinuous), also called avalanche. The measurement ends when a statistically relevant number of avalanches, for example 200 to 400 avalanche sliding downs, have been recorded. The camera images of the free-flowing impregnated particulate material are subsequently evaluated by digital image analysis. During the rotation powder analysis, the so-called avalanche angle as well as the time between two avalanches ("avalanche time") can be determined as parameters characteristic of free flowability. The avalanche angle is the angle of the material surface at which an avalanche occurs and therefore represents a measure of the height of a pile of free-flowing particulate material before this pile breaks up like an avalanche. The time interval between two avalanches corresponds to the time that has elapsed between the occurrence of two avalanches. A suitable tool for carrying out this rotational powder analysis and for determining the avalanche angle and the time interval between two avalanches is the Revolution Powder Analyzer manufactured by PS Prozesstechnik GmbH (Neuhausenstrasse 36, CH-4057 Basel). It is recommended to follow the operating instructions and recommendations enclosed with the device. The measurements are usually carried out at room temperature or at 20°C. In this case, the free-flowing impregnated particulate material can have an avalanche angle ranging, for example, from 40° to 90°, which is determined on the basis of a 100 mL test volume of material, using this device at 0.5 revolutions per minute and a cylinder with an internal depth of 35 mm and an internal diameter of 100 mm. The time between two avalanches can range, for example, from 2 seconds to 5 seconds and can constitute a characteristic of the free flowing nature of the free-flowing impregnated particulate material.
[0025] In a first embodiment of the method according to the invention, the particles X can be contacted with the at least one alkoxide in multiple steps carried out in the same manner, i.e. the at least one alkoxide can be contacted with the total amount of the particles X in multiple portions, a drying process being carried out in each case between the individual steps.
[0026] The second embodiment of the method according to the invention differs from the first embodiment in that the particles constituting the free-flowing powder, whether they are anhydrous or have a moisture content, are first moistened uniformly with water or further moistened with water to obtain particles X'. Thus, particles X' differ from particles X due to their moisture content or higher moisture content. The further steps in the second embodiment of the method according to the invention correspond to those in the first embodiment of the method according to the invention. During moistening, the desired moisture content of particles X' can be set, for example, in the range of 1% to 50% by weight. Thereby, particles X can be added to water or vice versa to form a mixture in each case. Generally, mixing is performed during and also after the addition. Examples of suitable mixing processes are based on the nature of the materials to be mixed and can therefore include, for example, shaking, stirring and / or kneading; in the preferred case of a mixed material in the form of a water-moistened free-flowing particulate material, powder mixing methods operating continuously or discontinuously known to the person skilled in the art, such as those described above in the first embodiment of the method according to the invention, are suitable. Preferably, water is added to the pre-supplied particles X, which optionally contain moisture. After the addition is completed, the wet mixed material may be given a further time, for example ranging up to 1 hour, before contacting the wet mixed material with at least one alkoxide. In this way, homogenization or uniform wetting of the mixed material can be ensured, in other words, in this way, a uniform distribution of water in the resulting particles X' can be ensured before they are subsequently contacted with at least one alkoxide. Generally, mixing is performed during and also after the addition.
[0027] The free flowability of particle X' can be examined by rotational powder analysis as described above, where particle X' can have an avalanche angle ranging, for example, from 40 degrees to 90 degrees, and the time between two avalanches can range, for example, from 2 seconds to 5 seconds, determined based on a test volume of 100 mL using a Revolution Powder Analyzer at 0.5 revolutions per minute and using a cylinder having an internal depth of 35 mm and an inner diameter of 100 mm.
[0028] In a second embodiment of the method according to the invention, particles X' and at least one optionally diluted alkoxide are brought into contact with each other to form a pulp-like, pasty or dough-like mass, a suspension or preferably a free-flowing impregnated particulate material. The at least one alkoxide constitutes the impregnating agent. Particles X' can be added to at least one alkoxide or vice versa. At least one alkoxide is preferably added to previously provided particles X. After the addition is finished, the reaction mixture may be further expediently given a time, for example ranging from 0.5 h to 3 h, before further process steps are carried out. In this way, completeness of the hydrolysis reaction and homogenization of the reaction mixture can be ensured. Generally, mixing is carried out during and also after the addition. Examples of suitable mixing processes are based on the nature of the materials to be mixed and can therefore include, for example, shaking, stirring and / or kneading; in the preferred case of a mixed material in the form of a free-flowing particulate material, powder mixing methods operating continuously or discontinuously known to the person skilled in the art are suitable, for example the procedures already mentioned for the first embodiment of the method according to the invention.
[0029] In a third embodiment of the method according to the invention, particles X, optionally containing moisture, are first suspended in an aqueous medium of water and a water-dilutable organic solvent. The suspension may, for example, consist of 50% to 95% by weight of the aqueous medium and 5% to 50% by weight of particles X, the weight percentages adding up to 100% by weight. The aqueous medium may, for example, consist of more than 0% to 95% by weight of water and 5% to less than 100% by weight of a water-dilutable organic solvent, the weight percentages adding up to 100% by weight. Examples of suitable water-dilutable organic solvents are in particular C1-C3 alcohols, in particular ethanol.
[0030] The suspension and at least one optionally diluted alkoxide are then brought into contact with each other. The suspension can be added to the at least one optionally diluted alkoxide or vice versa. The at least one optionally diluted alkoxide is preferably added to the previously provided suspension. The addition can be carried out continuously or discontinuously. After the addition is finished, the reaction mixture may be further expediently given a time, for example ranging from 0.5 h to 3 h, before further process steps are carried out. In this way, the completeness of the hydrolysis reaction and the homogenization of the reaction mixture can be ensured. Generally, mixing is carried out during the addition and also after the addition, for example by shaking and / or stirring.
[0031] The first and third embodiments of the method according to the invention are preferred embodiments.
[0032] As already mentioned, after hydrolysis, the process product obtained may be subjected to one or more further process steps, if necessary. Examples of such process steps include, in particular, solid-liquid separation, washing, drying and grinding. Such further process steps are carried out in the second and third embodiments, but generally also in the first embodiment. Thus, in the first embodiment of the method according to the invention, it is generally advantageous if successive drying and grinding are carried out. In the second and third embodiments, washing and solid-liquid separation are expediently carried out alternately, and then drying and grinding are carried out successively.
[0033] The solid-liquid separation can be carried out using methods known to those skilled in the art, such as decantation, squeezing, filtration, suction filtration, centrifugation, or similar operations, to at least largely separate the liquids (C1-C4 alcohols formed by hydrolysis, water, water-dilutable solvents) from the particulate material Z formed or washed during hydrolysis, resulting in a wet particulate material Z that still contains liquid.
[0034] Washing is expediently carried out with water, in which process water-soluble components, such as C1-C4 alcohols and / or water-dilutable organic solvents formed during hydrolysis, can be removed.
[0035] Drying may be carried out under ambient conditions in air without special measures or may be assisted by the application of reduced pressure and / or heat. Suitable drying temperatures are, for example, in the range of 50°C to 150°C. After drying, no further heat treatment, such as tempering at a temperature higher than the drying temperature, is necessary. Such heat treatments are generally and preferably not carried out.
[0036] Comminution can be accomplished, for example, in a mortar or by grinding (eg, using a rotor beater mill).
[0037] The method according to the invention is scalable in production scale and particulate material Z according to the invention can be efficiently produced in batch sizes of, for example, amounts of up to 5 tonnes.
[0038] The particulate material Z according to the invention has an antibacterial activity comparable to that of the materials known as antibacterial additives from WO 2021 / 084140(A2). The invention therefore also relates to the use of the particulate material Z according to the invention as an additive for the antibacterial treatment of metal surfaces, coatings, plasters, moulded bases, plastic films, plastic parts or plastic fibres in the form of plastic materials, synthetic resin products, ion exchange resins, silicone products, cellulosic products, foams, textiles, cosmetics, hygiene products and many other articles. Thereby, the cellulosic products can be selected, for example, from the group consisting of paper products, paperboard, wood fibre products and cellulose acetate, and the plastic materials can be selected, for example, from the group consisting of ABS plastic materials, PVC (polyvinyl chloride), polylactic acid, PU (polyurethane), poly(meth)acrylates, PC (polycarbonate), polysiloxanes, phenol formaldehyde resins, melamine formaldehyde resins, polyesters, polyamides, polyethers, polyolefins, polystyrenes, their hybrid polymers and mixtures thereof. In principle, the color of the material or object to be made antibacterial is arbitrary in this case. In particular, however, the material or object to be made antibacterial is preferably one having a light color, for example a color with a value L in the range of 50 to 90. * It is possible to select the particulate material Z according to the present invention with a color or brightness adapted to the material or object to be made antibacterial. It is also possible to use the particulate material Z according to the present invention in combination with a colorless or dark antibacterial active additive, for example, the particulate material Z according to the present invention in combination with an antibacterial active particulate carrier material with elemental silver and elemental ruthenium (for example, as known from WO 2021 / 084140(A2)). EXAMPLES
[0039] Reference Example 1 (Preparation of cellulose powder with elemental silver and elemental ruthenium according to embodiment 3 of WO 2021 / 084140(A2)): 75.6 g (445 mmol) of silver nitrate solid and 13.94 g of ruthenium nitrosylnitrate solution (ruthenium content 19.0 wt. %, 26.2 mmol of Ru) were dissolved in 416.8 g of deionized water, and the aqueous precursor solution thus obtained was mixed homogeneously with 211.2 g of cellulose powder (Vitacel® L-600 from Rettenmaier und Sohne GmbH&Co KG) to form an orange free-flowing particulate material. 705 mL of an aqueous hydrazine solution with a pH of 13.9 [4.19 g (131 mmol) of hydrazine and 81.81 g of a 32 wt. % sodium hydroxide solution (654.51 mmol of NaOH), the remainder being water] were metered in at room temperature with stirring at a metered addition rate of 30 mL / min. A black homogeneous pulp was formed, which became increasingly easier to stir over time. After the metering was finished, stirring was continued for 30 min until nitrogen evolution was no longer observed. The material was then filtered off by suction, washed with a total of 1,000 mL of water and dried in a drying cabinet at 105° C. / 300 mbar to a residual moisture content of 15% by weight. The silver content of the final product was 18.9% by weight and the ruthenium content was 1.0% by weight (relative to a residual moisture of 0% by weight) determined by ICP-OES.
[0040] The final product was ground in an agate mortar and the powder thus obtained appeared black to the human eye. After filling a colorless snap-cap vial to a filling height of 1 cm, a spectrophotometer (ColorLite sph900 spectrometer) was used to measure the concentration of the 44 L with a measurement geometry of d / 8° through the glass bottom of the snap-cap vial placed on the measurement head of the spectrophotometer. * value was determined.
[0041] Example 2 (Preparation of Z-type particulate material): 50 g of the black powder from Reference Example 1 containing 15% by weight of residual moisture was initially fed into a 6 L flask in contact with the ambient atmosphere and suspended in a mixture of 970 mL of ethanol and 35 mL of deionized water. 533.85 g of TTIP was dissolved in 400 mL of ethanol and added to the stirred suspension at a rate of 5 mL / min and then stirred for another 2 hours. The mixture obtained was then filtered and the light gray solid obtained was washed with 7 L of deionized water, dried at 105° C. for 24 hours (300 mbar) and then ground using an agate mortar. The silver content of the final product was 4.3% by weight and the ruthenium content was 0.2% by weight (relative to 0% by weight of residual moisture) was determined by ICP-OES. The powder thus obtained appeared light gray to the human eye. After filling colorless snap-cap vials to a fill height of 1 cm, a spectrophotometer (ColorLite sph900 spectrometer) was used to measure the concentration of 65 L at a measurement geometry of d / 8° through the glass bottom of the snap-cap vial placed on the measurement head of the spectrophotometer. * value was determined.
[0042] Example 3 (Preparation of Z-type particulate material): 50 g of the black powder from Reference Example 1 containing 15 wt. % residual moisture were dried at 105 ° C / 300 mbar. The obtained dried powder was first fed into a 6 L flask in contact with the ambient atmosphere and further processed as in Example 2. The silver content of the final product was 4.3 wt. % and the ruthenium content of 0.2 wt. % (for 0 wt. % residual moisture) were determined by ICP-OES. The powder thus obtained appeared light gray to the human eye. After filling a colorless snap-cap vial to a filling height of 1 cm, a spectrophotometer (ColorLite sph900 spectrometer) was used to measure the ruthenium content of 65 L with a measurement geometry of d / 8 ° through the glass bottom of the snap-cap vial placed on the measurement head of the spectrophotometer. * value was determined.
[0043] Example 4 (Preparation of Z-type particulate material): 10 g of the black powder from Reference Example 1 containing 15 wt.% residual moisture was mixed dropwise with 6.84 g of TTIP while stirring. The mixture was stirred for 10 min with air and then transferred to a ceramic bowl and dried at 105 °C / 300 mbar. The powder obtained was ground using an agate mortar. This sequence of steps was repeated 9 times, i.e. 68.4 g of TTIP was added in total. The silver content of the final product, 6.5 wt.% and the ruthenium content of 0.3 wt.% (for 0 wt.% residual moisture), were determined by ICP-OES. The powder thus obtained appeared light grey to the human eye. After filling a colorless snap-cap vial to a filling height of 1 cm, a spectrophotometer (ColorLite sph900 spectrometer) was used to measure the luminescence intensity of 56 L at a measurement geometry of d / 8° through the glass bottom of the snap-cap vial placed on the measurement head of the spectrophotometer. * value was determined.
[0044] Example 5 (Preparation of Z-type particulate material): 10 g of the black powder from Reference Example 1 containing 15 wt. % residual moisture were dried at 105 °C / 300 mbar. The obtained dried powder was further processed in the same way as in Example 4. The silver content of the final product, 6.5 wt. %, and the ruthenium content of 0.3 wt. % (relative to 0 wt. % residual moisture) were determined by ICP-OES. The powder thus obtained appeared light grey to the human eye. After filling a colorless snap-cap vial to a filling height of 1 cm, a spectrophotometer (ColorLite sph900 spectrometer) was used to measure the luminescence intensity of 56 L at a measurement geometry of d / 8° through the glass bottom of the snap-cap vial placed on the measurement head of the spectrophotometer. * value was determined.
Claims
1. 1. A particulate material Z consisting of 15% to 50% by weight of particles X of a water-insoluble support material T comprising elemental silver and elemental ruthenium, and 50% to 85% by weight of a solid Y at least partially disposed on said particles X, said solid Y being selected from the group consisting of aluminum oxide, aluminum hydroxide, aluminum oxyhydroxide, magnesium oxide, magnesium hydroxide, magnesium oxyhydroxide, calcium oxide, calcium hydroxide, calcium oxyhydroxide, silicon dioxide, silica, zinc oxide, zinc hydroxide, zinc oxyhydroxide, zirconium dioxide, zirconium (IV) oxyhydrate, titanium dioxide, titanium (IV) oxyhydrate, and combinations thereof.
2. 2. A particulate material Z according to claim 1, having a colour with a lightness L* in the range of 50 to 85.
3. 3. A particulate material Z according to claim 1 or 2, wherein the solid Y is formed as particles.
4. 4. Particulate material Z according to any one of claims 1 to 3, wherein the particles X have a silver+ruthenium weight percentage ranging from 0.1% to 50% by weight, with a silver:ruthenium weight ratio ranging from 1 part by weight to 2,000 parts by weight of silver:1 part by weight of ruthenium.
5. The particulate material Z according to any one of claims 1 to 4, wherein the carrier material T is water-swellable or capable of forming a hydrogel.
6. The particulate material Z according to any one of claims 1 to 4, wherein the support material T is selected from the group consisting of glasses, nitrides, high melting point oxides, silicates, plastic materials, modified or unmodified naturally occurring polymers, carbon substrates, and wood.
7. The particulate material Z according to any one of claims 1 to 4, wherein the support material T is silicon dioxide, titanium dioxide or cellulose.
8. A particulate material Z according to any one of claims 1 to 7, wherein said support material T is the same as or different from said solid Y.
9. 9. A method for preparing a particulate material Z according to any one of claims 1 to 8, comprising contacting particles X consisting of a water-insoluble support material T provided with elemental silver and elemental ruthenium with at least one C1-C4 alkoxide of aluminium, magnesium, calcium, silicon, zinc, zirconium and / or titanium in the presence of water in an amount at least sufficient for complete hydrolysis of said at least one C1-C4 alkoxide.
10. 10. The method of claim 9, wherein the at least one C1 to C4 alkoxide is a titanium tetraalkoxide.
11. 11. The method of claim 9 or 10, wherein the water is provided as atmospheric moisture, as the moisture content of particles X, and / or in liquid form.
12. 12. The process according to any one of claims 9 to 11, wherein the product obtained after the complete hydrolysis is subjected to one or more further processing steps selected from the group consisting of solid-liquid separation, washing, drying and grinding.
13. 13. The method according to any one of claims 9 to 12, wherein said particles X are directly contacted with said at least one alkoxide, or are first uniformly wetted with water, or are first suspended in an aqueous medium of water and a water-dilutable organic solvent.
14. Use of a particulate material Z according to any one of claims 1 to 8 or prepared according to the method of any one of claims 9 to 13 as an additive for the antimicrobial treatment of materials or objects to be made antimicrobial.
15. The use according to claim 14, wherein the material or object to be made antimicrobial has a chromatic or achromatic colour with a lightness L* in the range of 50-90.
Citation Information
Patent Citations
Colored spherical particulate and its production
JP1994047273A
Colored composite particle
JP1994200040A
Method of sterilization using sterilizing particle
JP2002191680A
Deodorizing / antibacterial / antifungal agent, method of preparation thereof, and member having deodorizing / antibacterial / antifungal agent on surface
JP2019063143A
Powder having multilayer film on its surface and process for preparing the same
WO1996028269A1
